Where she went - Forman, Gayle (New York Dutton, 2011)
Adam, now a rising rock star, and Mia, a successful cellist, reunite in New York and reconnect after the horrific events that tore them apart when Mia almost died in a car accident three years earlier
Sequel to: If I stay
1
Keywords: Cello -- Fiction; Emotional problems -- Fiction; Grief -- Fiction; Interpersonal relations -- Fiction; Rock music -- Fiction; New York (N.Y.) -- Fiction